Presencia de Salmonella spp. en tortugas motelo (Chelonoidis denticulata) del Centro de Conservación de Fauna Silvestre “Orillas del Zamora” de la ciudad de Loja, - Pardo Reyes, Angie Estefany (2022)
The purpose of this study was to determine whether Salmonella spp. was present in the food and associated risk factors that predispose to its appearance in the yellow-footed tortoises (Chelonoidis denticulatus), which have been rescued by the Ministry of Environment, Water and Ecological Transition (MAATE); and sent to Wildlife Conservation Center "Orillas del Zamora" (CCSF-OZ) in the city of Loja-Ecuador. To carry out this study, a population of species (37 animals) was analyzed, as well as individual samples were obtained by cloacal swabbing and preserved in Stuart transport medium. On the other hand, enrichment was performed in selenite-cystine broth and microbiological cultures which were performed in differential media to detect bacterial colonies. Additionally, to corroborate the existence of the bacillus, conventional biochemical tests for Salmonella were performed, together with Gram staining and specific antigen test kit. Of the 37 animals kept in the CCSF-OZ of the city of Loja in Ecuador, 18.92 % were positive for Salmonella spp. Likewise, the presence of specific antigens was demonstrated, finding in the samples the existence of somatic Salmonella Typhi O (1, 9, 12) and flagellar Salmonella H d. Consequently, these results indicate that Salmonella spp. bacteria is present in the population of yellow-footed turtles of the CCSF-OZ and elucidate the need to conserve these animals in their natural habitat and strictly prevent their commercialization, in order to avoid a considerable decrease of certain species and the progress of a possible zoonosis due to their presence. Key words: Contamination, Salmonella spp., yellow-footed turtles (Chelonoidis denticulatus), biochemical tests, antigens.